THE APPLICATION OF THE TRIPLE EXPONENTIAL SMOOTHING METHOD IN THE PREDICTION OF WAREHOUSE INVENTORY - Gusti Firanda; Rika Rosnelly (STMIK KAPUTAMA, 2023)
Prediction is an attempt to predict or predict something that will happen in the future by utilizing various relevant information in previous (historical) times through a scientific method. One of the applications of prediction in the business world is to predict future warehouse inventory based on the company's usage in the previous period. Prediction (Forecasting) is very helpful in planning and making decisions in an activity. Analysis is very important in learning, because research becomes more precise and focused. The problem faced by the company at this time is that the company has difficulty predicting warehouse inventory in the next period because there is no system that can be used by the company to predict. This predictive information will be very useful for companies in the process of planning clean water production to customers. In overcoming the problems mentioned above, a system is needed that can process data on goods that go in and out of the warehouse every period to get a prediction of warehouse inventory for the next period. To get optimal forecasting results, one method that can be used is the Triple Exponential Smoothing method. Triple Exponential Smoothing Method This method is a forecast method proposed by Brown, using quadratic equations .